Pre-Service and In-Service Teachers’ Perceptions on the Use of English Children’s Songs - Khumairo, Khurin In; Inayati, Dian; Asrining Tyas, Peptia (LPPM Universitas Advent Indonesia, 2022)
English children’s songs have been commonly used to teach English to young learners. Despite its popularity, few studies focus on its limitation. This study aims to explore pre-service and in-service teachers’ perceptions on the use of English Children’s songs to teach English to young learners. This study employed a qualitative descriptive method by involving two pre-service teachers, two in-service teachers, and four students. Data were collected through pre-service and in-service teachers’ interviews, students’ interviews, and classroom observation. The findings showed that English children’s songs offer numerous benefits for young learners in learning English. However, there were technical limitations such as the lack of internet connection and school facilities and non-technical limitations such as picking the right song for the students and providing various songs to prevent students’ boredom that faced by the pre-service and in-service teachers in using English children’s songs in the classroom. To overcome those limitations, pre-service and in-service teachers brought their laptops and speakers to play songs to students and downloaded songs to be played first. They were also very selective in choosing which songs the students could memorize easily and provided various songs.